Simultaneous detection of anthracene and phenanthrene on Ag-Au alloy nanoparticles/overoxidized-polypyrrole composite modified carbon electrode - Mailu, Stephen Nzioki (IOSR Journal of Applied Chemistry, 2019)
A simple and highly selective amperometric sensor for simultaneous determination of anthracene (AN) and phenanthrene (PHE) has been developed based on a composite of overoxidized-polypyrrole (PPyox) and Ag-Au alloy nanoparticles (Ag-AuNPs). UV-visible confirmed the formation of the Ag-Au alloy nanoparticles and transmission electron microscopy (TEM) revealed a rather uniform distribution of several nanometer-sized particles (20-30 nm). Voltammetric interrogations using ferricyanide redox probe showed that the composite (PPyox/Ag-AuNPs) had a higher catalytic effect compared to Ag-AuNPs and PPyox films. The sensor (PPyox/Ag-AuNPs composite-coated GCE) was interrogated with cyclic voltammetry (CV) and square wave voltammetry (SWV) in acetonitrile containing 0.1 M LiClO4. The sensing surface with the Ag-Au ratio of 1:3 was able to oxidize AN and PHE at different potentials when operated in the presence of both analytes. A successful elimination of the fouling effect by the oxidized products of AN and PHE was achieved at the modified electrode. The catalytic peak currents obtained from SWV increased linearly with increasing AN and PHE concentrations in the range of 30μΜto 312μΜ and 30μΜ to280μΜwith a detection limit of 23.05 μΜand 24.406 μΜ, respectively.
Keywords: Anthracene; Phenanthrene; Polyaromatic hydrocarbons; Overoxidized-polypyrrole; Composite